Effect of Rotary Swaging on Microstructure and Properties of Cr-Ni-Ti Austenitic Stainless Steel - Olga Rybalchenko; Vladimir Torganchuk; Georgy Rybalchenko; Natalia Martynenko; Elena Lukyanova; Alexey Tokar; Dmitry Prosvirnin; Vladimir Yusupov; Sergey Dobatkin (Metals, 2023)
In this study, Cr-Ni-Ti austenitic stainless steel was subjected to rotary swaging in various modes, followed by annealing. The effect of processing conditions on the resulting microstructure and, therefore, on the mechanical properties under static and cyclic loading was studied. After RS the formation of an ultrafine-grained predominantly twinned structure, with structural elements sized between 100–250 nm in Cr-Ni-Ti stainless steel, was observed. The stepwise temperature reduction during rotary swaging allows the manipulation of the microstructure transformations, which eventually leads to the desired properties of the steel. As a result, the ultimate tensile strength increased from 610 MPa to 1304 MPa when the elongation decreased from 40% to 10.5%, and the fatigue limit increased from 425 MPa to 700 MPa. The Cr-Ni-Ti steel is strengthened through the formation of an ultrafine-grained structure, twinning in austenite, and martensitic transformation. Subsequent annealing at a temperature 475 °C triggers the active precipitation of nanosized TiC carbides in the deformed steel. On one hand, the presence of these carbides increases the tensile strength up to 1938 Mpa, while on the other hand, slows down crack propagation with a slight decrease in ductility (ε = 8%) of the deformed sample. At the same time, dispersion hardening does not affect the fatigue limit of steel.